Hukum Pidana Mati Di Indonesia Berdasarkan Perspektif Hak Asasi Manusia Dan Alternatif Penegakan Hukum: Studi Kasus: Pidana Mati Ferdy Sambo (International Forum of Researchers and Lecturers, 2023)
Law is a tool for regulating people's lives with a coercive nature and requires people to follow existing rules. The law is made for the benefit of the people and contains the norms of life as a guide in society. Death penalty is a punishment with the most severe sanction scale for perpetrators of extraordinary crimes such as narcotics, premeditated murder, terrorism, and crimes against state security. However, the application of death penalty in Indonesia is controversial because it violates Human Rights (HAM) and the right to life guaranteed by the 1945 Constitution Article 28A paragraph (1). Even though there is an update in the latest Criminal Code (KUHP) which regulates probation for 10 years, pros and cons still occur in the application of death penalty. Various views on capital punishment exist, in which some consider human rights and the principles of justice. However, the death penalty must be applied carefully and pay attention to human rights.